Benefit of urban greenness on patients after an ischaemic stroke: mortality or recurrence? A registry-based cohort study - Raphaël Anxionnat; Nadine Bernard; Anne-Sophie Mariet; Sophie Pujol; Anne-Laure Parmentier; Kadiatou Diallo; Hélène Houot; Théophile Pierre; Yannick Béjot; Frédéric Mauny (PLoS ONE, 2026)
Background Whether living environment may influence outcome of stroke survivors remains to be elucidated. Aim This registry-based cohort study aimed to assess the relationship between urban greenness around the residence and one-year death or recurrence after a first-ever ischaemic stroke. Methods Patients with a first-ever ischaemic stroke who directly returned home were identified from the population-based registry of Dijon, France. For each patient, after geolocation of residential building, two greenness indices were calculated: the distance by road and pedestrian networks to the nearest public green space, and the area of green spaces within radii of 100 and 400 metres. Atmospheric NO 2 and PM 10 outdoor concentrations around the residence and deprivation index were assessed. Results During the 2005–2008 study period, 360 patients were identified and included (median age: 75 years-old (IQR: 63–83), 56% women). Fifteen died and 17 had recurrent stroke during the one year of follow-up. In adjusted models, the distance between public green spaces and patients’ residence was associated with stroke recurrence or death (HR = 1.26, 95% CI: 1.08–1.48, P < 0.01, for each 100 metre section of city network). In age-stratified analysis, this association remained significant only in patients aged 65–79 years (HR: 1.37, 95% CI: 1.10–1.71, P < 0.01). When considering separately stroke recurrence and death, this association remained significant for recurrence (HR = 1.30, 95% CI: 1.07–1.58, P < 0.01) but not for death (HR = 1.17, 95% CI: 0.89–1.52). Conclusion This study highlighted a beneficial influence of greenness on post-stroke recurrence in an urban area. These results indicate that urban planning policy could impact secondary prevention.